(untitled) (Research, Society and Development, 2020)
The purpose of this study was to develop active films of low-density polyethylene incorporated with different concentrations of oregano essential oil (1, 2, 3, 4, 5 and 6% w / w). The production of the films was carried out in a modular mono screw extruder and the antimicrobial activity was evaluated by the agar diffusion test. The films were analyzed for mechanical, optical and gaseous barrier properties to evaluate changes in the films due to the addition of an antimicrobial agent. As a result, it was found that the control film had a higher luminosity, compared to the others. The opacity was not affected. Saturation, however, had a tendency to transform more vivid colors, while the tone had a decrease tendency towards yellow. In terms of mechanical properties, elongation was not affected, Young’s modulus decreased and tension increased. The CO2 permeability decreased. There were no inhibition halos around the films.